Knowledge and Awareness of Dentists Working at Tertiary Care Hospital Towards Radiation Protection and Safety - Joshi, Ujjwal; Poudyal, Sijan; Pradhan, Megha; Gurung, Deepa; Chaulagain, Rajib (Journal of Karnali Academy of Health Sciences, 2020)
Background: Dental radiographs play a vital role in diagnosis and treatment planning of oral and maxillofacial regions through the use of ionizing radiation like X-Rays. These on the other hand also have harmful effects to our body. Even lesser amounts of radiation are harmful to the dental professionals and patients. Hence it is important to reduce exposure of radiation to prevent the harmful effects of ionizing radiation. Hence this present study was designed to assess the present knowledge and awareness towards radiation protection and safety among dental practitioners. Methods: A descriptive, cross-sectional study was designed and conducted among 100 study participants. A self-administered close-ended questionnaire was used to collect the data. The data obtained was analyzed and measured by descriptive analyses and cross tabulations by SPSS-16. Results: In this present study, 79(79%) of the participants thought that dental X-Ray is harmful whereas 21(21%) did not think it is harmful. Awareness of ALARA principle was seen among 88(88%) of the participants. About 77% of the participants considered thyroid as the most important organ to be protected during dental radiography while 90% of the participants confirmed to adhere to radiation protection in the future. Conclusion: Knowledge and awareness of dentists in the study towards radiation protection and safety was seen to be insufficient in many arenas. Regular workshops should be facilitated at both the institutional and national level for motivating them towards maintaining radiation safety protocol.